Riveting formula HDMI connector - HE FUQIAN (2016)
The utility model provides a riveting formula HDMI connector which characterized in that: including gluing core, pintle hook lock and a plurality of terminal, to glue the core trailing flank and be provided with the terminal manhole that the dislocation was arranged to a plurality of, top surface and bottom surface respectively are provided with one pintle hook lock locating hole, and the pintle hook lock locating hole is adjacent to be provided with gluey core draw -in groove, adjacent shell fragment trip and the terminal draw -in groove of being provided with on the terminal, be provided with the reference column on the pintle hook lock, the terminal passes through the terminal manhole that the riveting get into to correspond, and shell fragment trip card is in gluing heart draw -in groove, and the terminal draw -in groove is just to the pintle hook lock locating hole, and the pintle hook lock passes through the reference column card to be fixed at the pintle hook lock locating hole at terminal draw -in gro